ϒ production in p-Pb collisions at √sNN=8.16 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Köhler, Markus Konrad; Leardini, Lucia; Martin, Nicole Alice; Ohlson, Alice; et al. (Physics letters, 2020)
ϒ production in p-Pb interactions is studied at the centre-of-mass energy per nucleon-nucleon collision sNN=8.16 TeV with the ALICE detector at the CERN LHC. The measurement is performed reconstructing bottomonium resonances via their dimuon decay channel, in the centre-of-mass rapidity intervals 2.03<ycms<3.53 and −4.46<ycms<−2.96, down to zero transverse momentum. In this work, results on the ϒ(1S) production cross section as a function of rapidity and transverse momentum are presented. The corresponding nuclear modification factor shows a suppression of the ϒ(1S) yields with respect to pp collisions, both at forward and backward rapidity. This suppression is stronger in the low transverse momentum region and shows no significant dependence on the centrality of the interactions. Furthermore, the ϒ(2S) nuclear modification factor is evaluated, suggesting a suppression similar to that of the ϒ(1S). A first measurement of the ϒ(3S) has also been performed. Finally, results are compared with previous ALICE measurements in p-Pb collisions at sNN=5.02 TeV and with theoretical calculations.
Alice collaboration: S. Acharya, V. Anguelov, M. Arslandok, M.C. Danisch, V.J.G. Feuillard, P. Glässel, J. Kim, M. Kim, M.K. Köhler, L. Leardini, N.A. Martin, A. Ohlson, Y. Pachmayer, K. Reygers, R. Schicker, A. Schmah, M. Schmidt, J. Stachel, D.F. Weiser, B. Windelband, A. Yüncü [und 986 weitere]
Im Titel steht sNN unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt
Gesehen am 29.10.2020